Is Cystogastrostomy a Definitive Operation for Pancreatitis Associated Pancreatic Fluid Collections?. Issue 1 (24th February 2023) - Darwish, Muhammad Bassel; Logarajah, Shankar; McLaren, Patrick James; Campilan, Beatrice; Benzie, Annie Laurie; Cho, Edward; Osman, Houssam; Jeyarajah, D. Rohan
Abstract : Background: Pancreatic-enteric drainage procedures have become standard therapy for symptomatic pancreatic pseudocysts and walled-off pancreatic necrosis. The need for pancreatic resection after cyst-enteric drainage procedure in the event of recurrence is not well studied. This study aimed to quantify the percentage of patients requiring resection due to recurrence after surgical cystogastrostomy and identify predictors of drainage failure. Methods: A single-institution retrospective review was conducted to identify all patients undergoing surgical cystogastrostomy between 2012 and 2020. Demographic, disease, and treatment characteristics were identified. Failure of surgical drainage was defined as the need for subsequent pancreatic resection due to recurrence. Characteristics between failure and nonfailure groups were compared with identifying predictors of treatment failure. Results: Twenty-four cystogastrostomies were performed during the study period. Three patients (12.5%) required a subsequent distal pancreatectomy after surgical drainage. There was no difference in comorbidities between drainage alone and failure of drainage groups. Mean cyst size seemed to be larger in patients that underwent drainage alone versus those that needed subsequent resection (15.2 vs 10.3 cm, P =0.05). Estimated blood loss at initial operation was similar between groups (126 vs 166 mL, P =0.36). Conclusion: Surgical pancreatic drainage was successful in the initial management of pancreatic fluid collections. We did not identify any predictors of failure of initial drainage. There was a trend suggesting smaller cyst size may be associated with cystgastrostomy failure. Resection with distal pancreatectomy for walled-off pancreatic necrosis and pancreatic pseudocysts can be reserved for cases of failure of drainage.